The Low-Skill, Bad-Job Trap - Thomas, Alun (IMF Working Papers; Working Paper, 1994)
The paper explains how a country can fall into a 'low-skill, bad-job trap,' in which workers acquire insufficient training and firms provide insufficient skilled vacancies. In particular, the paper argues that in countries where a large proportion of the workforce is unskilled, firms have little incentive to provide good jobs (requiring high skills and providing high wages), and if few good jobs are available, workers have little incentive to acquire skills. In this context, the paper examines the need and effectiveness of training policy, and provides a possible explanation for why western countries have responded so differently to the broad-based shift in labor demand from unskilled to skilled labor.